Characteristics and Compliance of Tuberculosis Patients to the Use of Synthetic Drug and Herbal Medicine in Makassar City - Rusli Rusli; Rusdiaman Rusdiaman; Raymundus Chaliks; Rudy Hartono; Subriah Subriah; Agustina Ningsih; Zizka Zizka; Sainal Edi Kamal; Zulfiah Zulfiah; Rina Asrina; Rusmin Rusmin; Agust Dwi Djajanti (Humanistic Network for Science and Technology (HNST), 2021)
The high problem of TB in Indonesia is caused by, among other things, case finding and complete treatment, which are less rapid than the spread of the disease. The main goal of treating TB patients is to reduce mortality and morbidity and prevent transmission by curing patients. Characteristics of respondents, duration of TB treatment, resistance and side effects of TB drugs are problems to increase patient compliance in using these TB drugs. Treatment patterns and strategies are important in addressing the use of drugs that are good, correct and safe. The duration of tuberculosis treatment for 6 months, 9 months, and 12 months is the reason for the patient's non-compliance to treatment so that the achievement of successful treatment is difficult to avoid. The use of medicinal herbs as an alternative and to support modern medicine is an option in addressing this problem. Rapid urbanization in developing countries and the economic status of individuals also affect a person's susceptibility to infection. The TB burden follows the socio-economic level. The prevalence of tuberculosis in men is 3 times higher than in women. The same is happening in other countries. This happens because men are more exposed to TB risk factors such as smoking, exposure to air in the work environment and lack of non- compliance to taking medication. The purpose of this study was to analyze the characteristics of tuberculosis patients in carrying out treatment and patient compliance with the use of synthetic drugs and medicinal herbs in the city of Makassar. The type of research is quantitative research with a cross sectional study design. This study uses a survey method using a questionnaire instrument. The sample size in this study was 200 respondents. Statistical processing and analysis were univariate and multivariate. The results showed that there was a correlation between the socioeconomic characteristics of the respondents towards TB treatment using synthetic drugs and medicinal herbs and the level of adherence was still low.Keywords: characteristics; patient compliance; tuberculosis